Akuntabilitas Perumusan Kebijakan Publik dalam Musyawarah Perencanaan Pembangunan (MUSRENBANG): Studi pada Badan Perencanaan dan Pembangunan Daerah Kabupaten Malang - Maryanto Maryanto; Cahyo Sasmito; Muhammad Rifa’i (Universitas Islam Darul Ulum Lamongan, 2019)
The implementation of the development planning meeting (MUSRENBANG) in each region including the Malang district is often not optimal in the process so that the development development that is expected by the community through musrenbang does not have a good impact and does not give satisfaction to the residents. In the process of the Musrenbang, of course, it cannot be separated from the supervision and escort of the poor district government apparatus to begin with fiscal, program, process, legal and outgoing accountability in its implementation. So that the expectations of researchers through this paper can provide a brief summary of the accountability of the Musrenbang implementation process so far. This type of research uses a qualitative descriptive type of research. The results of this study on the implementation of policy formulation in the musrenbang in the poor district bappeda in the implementation process have been carried out well, directed, integrated and responsive to change, in accordance with what is already in the regent's vision and RPJM. However, this is also related to the supporting and inhibiting factors in the implementation process so far including among others citizen participation and the budget which are often the maximum constraints to the implementation of the musrenbang and insufficient budgets are also obstacles to its implementation.